The effect of nurses' COVID-19 vaccination status on fear of COVID-19: A cross-sectional study - Çiçek Gümüş, Ecem; Kocak, Hatice Serap; Beyoglu, Sakine; Gümüş, Ecem Çiçek (Routledge Journals, Taylor & Francis Ltd, 2024)
AimsThe aim of this study is to determine the effect of nurses' COVID-19 vaccination status on fear of COVID-19.MethodsThe research was conducted as a descriptive, correlational and cross-sectional study. A personal information form and the Fear of COVID-19 Scale were used for data collection. Data were collected using an online questionnaire. Descriptive statistics, t-test and ANOVA were used to evaluate the data.ResultsThe pre-vaccine and post-vaccine COVID-19 fear levels of the nurses were moderate. It was found that nurses who were women, were older, had a longer working period, and had COVID-19 experienced significantly higher fear. The vaccination rate was found to be 52.8%. When vaccination status and COVID-19 fear levels were evaluated, it was determined that vaccinated nurses had a significantly higher mean pre-vaccine fear score (p < .05). It was observed that the mean COVID-19 fear score decreased significantly after vaccination.DiscussionThe findings of this study showed that vaccination has an effect on the fear of COVID-19, that vaccination is important and that studies in this area need to be increased.
Keywords: Covid-19; Fear; Nurse; Vaccination; Public Health Nursing; Pandemic